Aplication of Ethnomedicine-Based Complementary Midwifery Care in a Pregnant Woman with Mild Anemia: A Case Study - Annisa, Annisa; Putri Ramadhanti, Indah; Audina, Dela; Fakhri, Ikhtiarina (Universitas Muhammadiyah Sidoarjo, 2026)
Anemia in pregnancy remains a significant public health problem. The 2023 Indonesian Health Survey reported a prevalence of 27.7% among pregnant women compared to 48.9% in 2018. Mild anemia can interfere with maternal well-being and pregnancy outcomes if not properly treated. Complementary ethnomedicine therapy using natural plants rich in iron, such as red dragon fruit and moringa leaves, has the potential to increase hemoglobin (Hb) levels. The purpose of this study was to evaluate the effect of complementary ethnomedicine therapy on hemoglobin levels in pregnant women with mild anemia. The research method was a case study conducted in February 2024 at the Midwife Independent Practice in Limapuluh Kota District. The subjects were primigravida women in their second trimester who were diagnosed with mild anemia based on clinical signs and laboratory tests. Primary data were collected through physical assessment and Hb measurement. The intervention consisted of complementary therapy using red dragon fruit and moringa leaves, administered daily for two weeks along with standard nutritional advice. Hb levels were measured before and after the intervention. Hb levels before the intervention were 10.2 g%, and Hb levels after the intervention were 11.3 g/dL. This represents an increase of 1.1 g%. In conclusion, treatment was provided according to the mother's needs. At the second visit, the mother did not have anemia. Complementary ethnomedical therapy using dragon fruit and moringa leaves can help prevent mild anemia in pregnant women.